2014
DOI: 10.5603/kp.2014.0212
|View full text |Cite
|
Sign up to set email alerts
|

2014 ESC Guidelines on diagnosis and management of hypertrophic cardiomyopathy

Abstract: Рабочая группа по диагностике и лечению гипертрофической кардиомиопатии Европейского общества кардиологов (ESC)Авторы/члены рабочей группы: perry M. Elliott* (Председатель) (великобритания) Aris Anastasakis (Греция), Michael A. borger (Германия), Martin borggrefe (Германия), Franco Cecchi (Италия), philippe Charron (Франция), Albert Alain Hagege (Франция), Antoine Lafont (Франция), Giuseppe Limongelli (Италия), Heiko Mahrholdt (Германия), William J. McKenna (великобритания), Jens Mogensen (дания), petros Nihoy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
321
0
34

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 217 publications
(360 citation statements)
references
References 497 publications
5
321
0
34
Order By: Relevance
“…Compared with the ASA method, limited ischemic necrosis in the EVOH septal ablation procedure may cause a significant decrease in efficacy especially in patients with a septum thickness of 25 mm or more. Current guidelines emphasize the preference of surgical myectomy rather than ASA in patients with significant thick septum [1,2]. In our series, the septum thickness of our 3 patients was over 25 mm, and one of them was treated with surgical septal myectomy and mitral valve replacement.…”
Section: Details Of the Baseline And Follow-up Echocardiographic Analmentioning
confidence: 72%
See 1 more Smart Citation
“…Compared with the ASA method, limited ischemic necrosis in the EVOH septal ablation procedure may cause a significant decrease in efficacy especially in patients with a septum thickness of 25 mm or more. Current guidelines emphasize the preference of surgical myectomy rather than ASA in patients with significant thick septum [1,2]. In our series, the septum thickness of our 3 patients was over 25 mm, and one of them was treated with surgical septal myectomy and mitral valve replacement.…”
Section: Details Of the Baseline And Follow-up Echocardiographic Analmentioning
confidence: 72%
“…In our study, we revealed a reduction in left atrium volume and volume index and this decline has continued throughout the follow-up. Therefore, showing the LV and LA reverse remodeling is one of the most important aspects of our work.ASA has a principal role in the current management of drugrefractory HOCM patients with LVOT obstruction and became the treatment of choice in most patients[2]. The main reason compelling us to use EVOH for septal ablation was to avoid remote infarction that may be noted after alcohol injection.…”
mentioning
confidence: 99%
“…7 They found that previous algorithms based on binary variables did not take into account the effect size of individual risk factors, and so had a modest discriminatory power between high and low risk. Therefore, sudden cardiac death risk assessment using HCM Risk-SCD 8 is recommended.…”
Section: To the Editormentioning
confidence: 98%
“…The present clinical case illustrates several interesting clinical aspects related to natural history and management of left ventricular outflow tract obstruction: (1) the differential diagnosis between hypertensive heart with obstruction versus Hypertrophic Cardiomyopathy (HCM) [1]; (2) the difficulties involved in its medical treatment [2]; and (3) the temporary effect of the different strategies for reducing obstruction in HCM [3,4]. Finally the indication of invasive techniques can occasionally lead to iatrogenic effects particularly in the elderly patients.…”
Section: Dear Editormentioning
confidence: 99%